A Studi of the Historical and Spiritual Values of the Muharram Cultural Kirab Tradition in Payaman Kudus Village from A Hadith Perspective - Putri, Octaviany Widya; Friyadi, Arif (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
The Muharram cultural procession tradition is one of the activities carried out in Payaman Village, Mejobo District, Kudus Regency. This activity is maintained and preserved as a form of respect and reminder of the ancestors of the Payaman Village community. This research aims to show that the implementation of this cultural procession is based on Islamic principles, which play a role in strengthening the relationship between residents and as an expression of gratitude to God for all the blessings given to them. The method used in this research is a descriptive qualitative approach, with the collection of two types of data: primary and secondary data. Primary data was obtained through interviews, while secondary data was collected from literature studies, websites, and other sources relevant to the topic discussed. The results show the existence of a cultural kirab that contains Islamic values and hadith, which serve as the basis for understanding social religious phenomena. In addition, the month of Muharram is interpreted as a symbol of awakening. This article is expected to develop the knowledge and understanding of the community, especially the younger generation, so that we can always maintain and preserve the existing culture.